A Case Study of The Finger Grip Relaxation Intervention on Lowering Pain Scale in Appendicitis Patients - Safariyah, Erna; Salsabilla, Nadya; Setiawan, Henri (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: Pain is the most common symptom that is often found in patients with appendicitis. One of the non-pharmacological interventions that can do to treat pain is Finger Grip Relaxation. Objective: This case study is to describe the finger grip relaxation technique intervention to reduce pain in appendicitis patients. Methods: This study uses a case study design with an evidence-based practice implementation approach focusing on nursing interventions. The research was conducted at the BLUD RSU Banjar City on 27-31 May 2022. The participant in this study was Mrs.C, a 35-year-old female who complained of right lower abdominal pain. The process of assessing and establishing a diagnosis focused on the main problem. Objective and subjective data become a reference for periodic evaluation of nursing implementation. The instrument used is a numeric rating scale. Results: the patient acknowledged that the pain decreased after the finger grip relaxation intervention. Conclusion: Finger grip relaxation intervention should be suspected to be effective in reducing pain in appendicitis patients, as evidenced by the subjective patient. Theoretically, this research does not conflict with previous research, so it can be a reference in future research. Recommendation: Clinically, finger grip relaxations can be an alternative intervention to reduce pain in patients with chronic diseases such as appendicitis in hospitals and health centers